Optimized fast charging protocol for cylindrical lithium‐ion battery based on constant incremental capacity algorithm. (14th September 2020) - Lao, Li; Wu, Shangquan; Zhang, Qingchuan
Summary: Reducing the charging time for electric vehicles (EVs) is considered as a crucial factor to promote consumer interest and improve the competitiveness of EVs in the automotive market. Therefore, the investigation of fast charging protocol becomes increasingly important. In this work, a novel self‐adaptive fast charging protocol for cylindrical lithium‐ion battery is proposed based on constant incremental capacity ( dQ/dV ) algorithm, the charging current of which is adaptively adjusted by the intrinsic properties of battery. The cycle test results show that the battery using the new fast charging protocol maintains a capacity of about 90% after 1150 cycles, indicating that the proposed charging protocol can improve the cycle life of the battery, while decreasing the charging time. The fatigue analysis has shown that the capacity fade results predominantly from the loss of active lithium ion and degradation of anode. The anode potential evaluation results show that the anode potential is always greater than zero volt with the proposed fast charging protocol, which avoids lithium deposition. Meanwhile, the post‐mortem results of cycled battery indicate that the battery using the proposed charging protocol generate no lithium deposition on anode. Abstract : A new fast charging method for cylindrical Li‐ion battery is proposed based on constant incremental capacity algorithm. The method improves battery life by inhibition of lithium deposition. The method is self‐adaptive to adjust the charging current. Battery using the new fast charging protocol maintains about 90% capacity after 1150 cycles, which far exceeds that of batteries using the constant current fast charging method.